Solutions of the system of maximum difference equations 1 1 3 3 1 1 max , ; max , n n n n n n n n y x x y xx yy + + − −   =   =   - Dağıstan Şimşek; Burak Oğul (MANAS: Journal of Engineering)
This paper deals with the behaivour of the solutions of the max‐type system of difference equationsxn+1=max{1/xn-3,yn/xn}, yn+1=max{1/yn-3,xn/yn},where the initial conditions are positive real numbers.